Effect of thermal aging procedure on the microhardness and surface roughness of fluoride containing materials (Annals of Medical Research, 2021)
Aim: The aim of this in vitro study was to evaluate the thermal aging effect on microhardness and surface roughness of fluoride containing restorative materials.Material and Methods: In this study, a bioactive material (Activa Bioactive Restorative, Pulpdent, Watertown, MA, USA), a giomer (Beautifil II, Shofu, Kyoto, Japan), a nanohybrid composite (Charisma Smart, Heraeus Kulzer, Germany), a resin-modified glass ionomer (Ionoseal, VOCO, Germany), and a bulk-fill glass-hybrid material (Equia Forte, GC, Tokyo, Japan) were used. 10×2 mm discs were prepared (n=10) and then polymerized. Only for bulk-fill glass-hybrid specimens, one layer of coat was applied on top surfaces and light cured. Before and after thermal aging procedures, initial and final surface roughness and microhardness values were evaluated. One-Way ANOVA test was used for the statistical analysis (p0.05).Results: Thermal aging did not affect the surface roughness of restorative materials statistically (p>0.05). After thermal aging when the bottom surface of Equia Forte compared to Activa Bioactive and Beautifil II in terms of microhardness values, a statictical significant difference was observed (p0.05).Conclusion: Even before and after thermal aging procedures, successful results can be achieved with bulk-fill glass-hybrid material.
Keywords: Cariostatic agents; hardness tests; mechanical properties; thermal analysis; surface properties